Inhibition of platelet‐derived growth factor receptorβ by imatinib mesylate suppresses proliferation and alters differentiation of human mesenchymal stem cells in vitro - Fierro, F. (Blackwell Publishing Ltd, 2007)

(untitled) (Cell Prolif)
Abstract.  Objectives: Recent data show that Imatinib mesylate (IM) also affects haematopoietic stem cells (HSC), T lymphocytes and dendritic cells that do not harbour constitutively active tyrosine kinases. Materials and methods: We evaluated possible effects of IM on human bone marrow‐derived mesenchymal stem cells (MSC) in vitro. Results: Screening the activity of 42 receptor tyrosine kinases revealed an exclusive inhibition of platelet‐derived growth factor receptorβ (PDGFRβ). Analysis of downstream targets of PDGFRβ demonstrated IM‐mediated reduction of Akt and Erk1/2 phosphorylation. Culture of MSC with IM led to the reversible development of perinuclear multi‐vesicular bodies. The proliferation and clonogenicity of MSC were significantly reduced compared to control cultures. IM favoured adipogenic differentiation of MSC whereas osteogenesis was suppressed. The functional deficits described led to a 50% reduction in the support of clonogenic haematopoietic stem cells, cultured for 1 month on a monolayer of MSC with IM. Conclusion: In summary, inhibition of PDGFRβ and downstream Akt and Erk signalling by IM has a significant impact on proliferation and differentiation of human MSC in vitro.